Factors Influencing Green Building Development in Kazakhstan - Daniyar Assylbekov; Abid Nadeem; Md Aslam Hossain; Gulzhanat Akhanova; Malik Khalfan (Buildings, 2021)
Green buildings have been actively spreading as a solution for sustainability issues of the construction industry in at least the last two decades. As green building practices unfold in developing countries, the need of identifying factors that both hinder and drive its spread rises. Multiple studies reveal a general inconsistency among results in different parts of the world, caused by each country’s environmental, economic, and social conditions. Taking into account the experience of developing international green buildings and the current state of green building development in Kazakhstan, this study aims to spread the understanding of the factors that hinder and have the potential to drive the development of green buildings in Kazakhstan. A questionnaire survey was carried out among 38 industry experts in Kazakhstan to accomplish study objectives. Multiple data analysis methods were used to identify correlations among groups of experts and rank the factors. The results revealed a lack of skill/experience, a lack of government support, and the high cost of sustainable materials and products as the most crucial barriers. Water and energy efficiency, improved health of occupants, comfort, and satisfaction were identified as the most influential drivers. By expanding knowledge on factors affecting the implementation of green buildings, the study uncovered common trends in the responses of professionals, providing valuable information for field professionals and suggesting future research recommendations.